2008
DOI: 10.1088/0741-3335/50/7/074010
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of auroral radio emission mechanisms by laboratory experiment

Abstract: This version is available at https://strathprints.strath.ac.uk/63095/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 29 publications
6
40
0
Order By: Relevance
“…2,7,13 A laboratory experiment and simulations in which this type of distribution was produced showed that it did indeed generate waves with many of the properties of AKR. [14][15][16][17][18][19] In the simulations and in the laboratory experiment an electron beam with initial finite pitch spread ␣ = v Ќ / v z was injected into an increasing axial magnetic field. Through conservation of magnetic moment, a progressive magnetic mirroring of the beam resulted in the conversion of axial momentum into perpendicular momentum yielding a horseshoe shaped velocity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…2,7,13 A laboratory experiment and simulations in which this type of distribution was produced showed that it did indeed generate waves with many of the properties of AKR. [14][15][16][17][18][19] In the simulations and in the laboratory experiment an electron beam with initial finite pitch spread ␣ = v Ќ / v z was injected into an increasing axial magnetic field. Through conservation of magnetic moment, a progressive magnetic mirroring of the beam resulted in the conversion of axial momentum into perpendicular momentum yielding a horseshoe shaped velocity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, the cyclotron-maser instability is presumed to be driven by an electron horseshoe or modified horseshoe-ring distribution. Scaled laboratory experiments have demonstrated the potential for such horseshoe distributions to generate narrowband cyclotron-maser emission at GHz frequencies over distances of a few meters [21][22][23][24][25].Although the generation mechanism is well established, there remain important questions with regard to how the radiation may propagate within the parent auroral density cavity and ultimately escape [26]. Cairns et al [27] have demonstrated how the radiation, generated just below the electron cyclotron frequency, may successfully couple onto the upper branch of the plasma dispersion relation and escape.…”
mentioning
confidence: 99%
“…In all cases, the cyclotron-maser instability is presumed to be driven by an electron horseshoe or modified horseshoe-ring distribution. Scaled laboratory experiments have demonstrated the potential for such horseshoe distributions to generate narrowband cyclotron-maser emission at GHz frequencies over distances of a few meters [21][22][23][24][25].…”
mentioning
confidence: 99%
“…The emission mechanism they suggested is an electron cyclotron maser mechanism, where the electron distribution function is governed by the hole and may be different from the much studied horseshoe distribution (Ergun et al, 2000a). Similar systems have been seen to emit radio waves in laboratory plasmas (Lindberg, 1993;Volwerk, 1993;Brenning et al, 2006), although the electron beam energies were far below those used in dedicated cyclotron maser experiments (McConville et al, 2008) and simulations (Speirs et al, 2014). The simulations reported here are electrostatic and can therefore not be used to study radiation processes, which would require electromagnetic models.…”
Section: Conclusion and Discussionmentioning
confidence: 99%